Social Work Glossary: Mental Health - Stefan Brown (Social Work and Society)
Mental health concerns itself with the operation of the mind including thoughts, emotions, affect and cognitions. As these are in themselves complex entities the way in which we understand mental health remains challenging. Mental health as a term is used broadly in professional practice, academic writing and popular media. It can be contrasted with other terms that have been used to understand the health of the mind, like mental illness which is deficit focused and medically orientated and the term mental disorder which in some settings provide a medical-legal definition. Additionally there are lay interpretations of the term mental health which are reflected in everyday beliefs, influenced by the media.Â  Terms such as 'psycho,' "˜barmy' and 'madness' are examples of the everyday references to mental health within the public discourse. While lay definitions are often discriminatory and stigmatising they reveal the underlying opinions and attitudes that exist when mental health is talked about. These definitions should not be discounted as they reveal how everyday attitudes around mental health are informed by language, the media and personal experience.Â  The variety of ways of understanding the term mental health tells us that the term mental health is far from clear and does not hold a common shared meaning. The World Health Organisation considers that mental health is less defined by its deficit - mental illness/ mental disorder but is understood more positively. In its work the World Health Organisation notes that mental health and in particular mental distress is evident in all societies and in its attempt to provide a globally acceptable definition of mental health it highlights that the definition of mental health includes a"state of well being, being able to realise one's own potential and is able to cope with the normal stresses of life, can work productively and fruitfully and make a contribution to his or her community" (WHO 2010 p6).Â  This definition positively avoids medical or legal terminology but does face some challenges like the practical application of well-being which can be subject individual interpretation.